SISTEM PENUNJANG KEPUTUSAN RENTAL MOBIL DENGAN MENGGUNAKAN METODE FUZZY - Rifaldi Zulkarnaen; Dudih Gustian (INFOKOM (Informatika & Komputer), 2021)
Car rental is a business engaged in car rental services. Every year the market of hot-selling car rental is hunted by consumers especially in the west and on holidays and certainly the prices for rent are certainly various in accordance with rental prices distance or different days different. But often the difficulties in the field of management bookkeeping or data collection of consumer queues with a manual system, both in the field of bookings and bookkeeping data needed. So the author conducts research using fuzzy logic method which method is very helpful in taking decisions when consumers need a vehicle and are very helpful to the management of the company. This method is accurate with 90% accuracy, this method uses the mamdani method that is using a min-max operation or max-product. To get output, it is expected that this research will provide a solution in arranging ordering data, time of departure and selection of vehicles on the car's interior so that data management can be optimized.